Religion after Deliberative Democracy - Stanley, Timothy (Routledge Studies in Religion and Politics Ser., 2022)
Cover -- Half Title -- Series -- Title -- Copyright -- Dedication -- Contents -- Acknowledgments -- Introduction -- 1 Pragmatist Faith in Deliberative Democracy -- 1. Beyond Pragmatist Secularism, Relativism, and Narcissism -- 2. Pragmatist Truth Claims -- 3. The Persistence of Religious Resentment -- 2 The Public Sphere as Utopia -- 1. Religion in Habermas's Public Hermeneutics -- 2. Ricoeur's Hermeneutics of Utopia -- 3. Shattering Dominant Ideologies -- 3 Applying Arendt's Vita Activa to Religion -- 1. Intersubjective Plurality in the Vita Activa -- 2. Arendt's Religion -- 3. After Arendt -- 4 Comparative Political Theology of Sovereignty -- 1. Toward Comparative Political Theology -- 2. Scholem's Messianism -- 3. Qutb's Hakimayyah -- 4. Suspending Theocracy -- 5 Religion in Deliberative Democratic Systems Theory -- 1. New Developments in DDST -- 2. Precluding Religion in DDST -- 3. Religion after Deliberative Systems -- Conclusion -- Epilogue: Bonhoeffer's Anti-Judaism -- Bibliography -- Index.